SCALE-UP STUDIES ON IMMOBILIZATION OF LACTOPEROXIDASE USING MILK WHEY FOR PRODUCING ANTIMICROBIAL AGENT - Al-Baarri, A.N.; Agawa, M.; Hayakawa, S. (Diponegoro University, 2010)
Hypothiocyanite (OSCN–), produced by lactoperoxidase (LPO) in the presence of SCN– and H2O2,inhibits the growth of bacteria. This inhibition is called by LPO system (LPOS). Our laboratory scalestudy in previous experiment showed that whey immobilized on SP-Sepharose Fast Flow (SP-FF) couldproduce OSCN– continuously. Then, the purpose of this study is to scale up continuous production ofOSCN– using immobilized whey. Immobilized whey was generated by circulating various amounts ofwhey through SP-FF. To generate OSCN–, 10 ml of the substrate solution containing 0.5 mM SCN– and0.5 mM H2O2, was circulated through immobilized whey and followed by washing with pure water. Thenext cycle was done by circulating a fresh 10 ml of substrate solution at the same concentration. Theresult indicated that a stable immobilization efficiency of more than 90% was achieved in the SP-FFcirculated with 300 ml or less of whey per gram of SP-FF. When stored at 4˚C, immobilized wheyretained 80% LPO activity until 3 weeks storage. The reaction solution discharged from immobilizedwhey was observed to contain approximately 0.4 mM OSCN–. The experiment using 1.0 g ofimmobilized whey produced a stable 0.4 mM OSCN– production and antimicrobial activity for at least 6cycles. The increase in resin volume accompanied by the increase in whey volume resulted the extensionof a stable OSCN– production. The experiment using recycled SP-FF did not affect to the stability ofOSCN– production and antimicrobial activity. These results may open the way for the large-scaleproduction of OSCN−.